Investigations on thermal properties of microencapsulated phase‐change materials with different acrylate‐based copolymer shells as thermal insulation materials. Issue 31 (15th April 2019) - Ma, Yanhong; Xie, Qifei; Wang, Xinzhong
ABSTRACT: A series of microencapsulated phase‐change materials (micro‐PCMs) with binary cores and acrylate‐based copolymer shells were prepared. The micro‐PCMs contained octadecane and butyl stearate as binary‐core materials. Allyl methacrylate, ethylene glycol dimethacrylate, 1, 4‐butanediol diacrylate (BDDA), and 1, 6‐hexanediol dimethacrylate were respectively introduced to copolymerize with divinylbenzene (DVB) to form different microcapsule shells. In this work, the influence of the types of core and shell materials and core–shell weight ratios on the thermal properties of micro‐PCMs was studied. The chemical structures, morphologies, thermal properties, and thermal insulation properties of the wallboards were all tested and discussed. Scanning electron microscope photographs show that these micro‐PCMs have relatively spherical profiles and compact surfaces with diameters ranging from 10 to 80 μm. Differential scanning calorimetry results indicated that their microencapsulation efficiency ranged from 48 wt % to 80 wt %. A thermogravimetric analysis demonstrated that these micro‐PCMs can ensure their thermal stability below 210°C. Finally, a thermal insulation wallboard fabricated with synthesized P(BDDA‐ co ‐DVB) micro‐PCMs showed excellent thermal energy storage performance, keeping the temperature fluctuation within 2.5°C. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47777. Abstract :